The Role of the Vitamin D Receptor in the Pathogenesis, Prognosis, and Treatment of Cutaneous Melanoma - Becker, Alyssa L.; Carpenter, Evan L.; Slominski, Andrzej T.; Indra, Arup K. (Frontiers in Oncology, 2021)
Melanoma is the malignant transformation of melanocytes, and represents the most lethal form of skin cancer. While early-stage melanoma localized to the skin can be cured with surgical excision, metastatic melanoma often requires a multi-pronged approach and even then, can exhibit treatment resistance. Understanding the molecular mechanisms involved in the pathogenesis of melanoma could lead to novel diagnostic, prognostic, and therapeutic strategies, which would ultimately decrease morbidity and mortality. One emerging candidate that may have value as both a prognostic marker and in a therapeutic context is the vitamin D receptor (VDR). VDR is a nuclear steroid hormone receptor activated by 1,25 dihydroxy-vitamin D3 (calcitriol, 1,25(OH)2D3). While 1,25 dihydroxy-vitamin D3 is typically thought of in relation to calcium metabolism, it also plays an important role in cell proliferation, differentiation, programmed-cell death as well as photoprotection. This review discusses the role of VDR in the cross-talk between keratinocytes and melanocytes during melanomagenesis and summarizes the clinical data regarding VDR polymorphisms, VDR as a prognostic marker, and potential uses of vitamin D and its analogs as an adjuvant treatment for melanoma.